2021
DOI: 10.3390/children8020093
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technologies to Support Early Screening of Autism Spectrum Disorder: A Systematic Review

Abstract: The aim of this systematic review is to identify recent digital technologies used to detect early signs of autism spectrum disorder (ASD) in preschool children (i.e., up to six years of age). A systematic literature search was performed for English language articles and conference papers indexed in Pubmed, PsycInfo, ERIC, CINAHL, WoS, IEEE, and ACM digital libraries up until January 2020. A follow-up search was conducted to cover the literature published until December 2020 for the usefulness and interest in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
(217 reference statements)
0
5
0
Order By: Relevance
“…Among the studies reporting psychometric information (n = 15), 8 reported sensitivity and specificity values equal to or greater than 75%. However, it should be noted that sensitivity values below this threshold may not indicate poor psychometric properties as the tool may be reliable for detecting specific subgroups of ASD patients [ 11 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies reporting psychometric information (n = 15), 8 reported sensitivity and specificity values equal to or greater than 75%. However, it should be noted that sensitivity values below this threshold may not indicate poor psychometric properties as the tool may be reliable for detecting specific subgroups of ASD patients [ 11 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other reviews have mainly focused on the psychometric properties of telemedicine for ASD diagnostics [ 23 , 42 , 43 ]. For instance, Desideri et al [ 11 ] reviewed the application of telemedicine for the early screening of children with ASD under 6 years of age along with psychometric properties. However, none of the previous literature reviews have comprehensively examined the application and observed behavioral indicators of telemedicine for the screening and diagnosis of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Various psychometric screening instruments have been proposed and applied to improve early detection and diagnosis in ASD (Levy et al, 2020;Petrocchi et al, 2020). In recent years, information and communication technologies (ICT) related products such as smartphones, tablets, eye trackers, or robots (Desideri et al, 2021), home video (Tariq et al, 2018), multi-modular AI approaches (Abbas et al, 2020), and machine learning strategies (Achenie et al, 2019) have offered easier and comparable alternative psychometric screening for ASD. However, these psychometric screening methods are not readily implemented during infancy.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature that recognizes the role of telemedicine in ASD diagnosis and interventions, especially during the COVID-19 emergency [ 18 , 21 , 22 , 23 , 24 , 25 ]. For instance, Narzisi [ 18 ] proposed a telemedicine working model for the preliminary diagnosis and intervention of children with ASD, using synchronous and asynchronous transmission.…”
Section: Introductionmentioning
confidence: 99%